Football in Turkey during the Erdoğan regime. (17th August 2020) - Irak, Dağhan
ABSTRACT: Since Islamist-conservative Recep Tayyip Erdoğan took over power in Turkey, the country has gone through a massive social transformation. Football, the quintessential form of entertainment in Turkey which has always had its ties with politics, has also been affected by this change. Especially after the Gezi Protests, in which the supporters of three major Istanbul clubs participated, to express their discontent over Erdoğan's autocratic tendencies and interventions on secular lifestyles, the ruling party's intervention in football accelerated. The new regime employed heavy policing, a controversial e-ticket scheme, and criminal court cases to suppress dissent in the stadiums, and also sponsored two pro-regime teams of its own that reached success but not popularity. The regime's every move concerning football has been contested by the middle-class, secular football fans of Istanbul's pro-opposition neighbourhoods. This paper discusses the historical and sociological origins of Erdoğan's recurring defeats in the football field versus Stambulite fans.